The effect of post-ultraviolet light curing on the accuracy of direct-printed aligners: an in vitro study - Kanase Anup; Misra Vaibhav; Sobti Roohi (Sciendo, 2024)
Direct-printed aligners have proven to be more cost effective and accurate. However, the post-curing process might affect their dimensional accuracy, leading to unwanted tooth movement. The present study aimed to investigate the effect of different post-curing durations on the location specific accuracy of direct-printed aligners.